Method for constructing thickness-controllable coating layer in solution phase

By using the coating substrate material, coordination agent and organometallic salt in the non-aqueous solvent, a metal-containing cladding layer with controllable thickness on the surface of the core-shell structure material is solved, and the water sensitivity and precipitation control of the material in high-energy energy storage devices is improved, and the stability and electrochemical properties of the material are improved.

CN119650609APending Publication Date: 2025-03-18INST OF CHEM CHINESE ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311204738.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the preparation process of core-shell structural materials, how to control the precipitation method and precipitation speed of metal ions so that their growth process meets the needs of heterogeneous nucleation, especially in high-energy energy storage devices such as lithium-ion batteries, the material is sensitive to water, and the wet coating process can easily lead to rapid attenuation of material capacity.

Method used

A coating substrate material, coordination agent and initiator are added to the non-aqueous solvent, and an organometallic salt is added to the mixture liquid. A metal-containing coating layer is formed on the surface of the coating substrate material through stirring and reaction. The process is simple and the reaction conditions are mild, so accurate and non-destructive coating structure can be achieved.

Benefits of technology

The surface of the nuclear material is accurately and non-destructively treated in a non-aqueous solvent, forming a coating with controllable thickness, improving the stability and electrochemical properties of the material, and is suitable for the cathode material of high-energy energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650609A_ABST
    Figure CN119650609A_ABST
Patent Text Reader

Abstract

The invention discloses a method for constructing a thickness-controllable coating layer in a solution phase. The method provided by the invention comprises the following steps: adding a coated substrate material, a coordination agent and an initiator into a non-aqueous solvent to obtain a mixed solution; and adding an organic metal salt into the mixed solution, and stirring for reaction to form a metal-containing coating layer on the surface of the coating substrate material. The coating method provided by the invention is simple and easy to implement, the raw materials are easy to obtain and low in price, the reaction conditions are mild, large-scale production can be realized, and the obtained coating layer is continuous, complete and uniform and controllable in thickness. When the obtained core-shell structure material is used for a lithium ion battery, the cycling stability and the rate capability of a positive electrode material can be effectively improved, and the core-shell structure material has a very high use value and a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a method for constructing a coating layer with controllable thickness in a solution phase. Background Art

[0002] The core-shell structure has a special spatial configuration. Combined with the design of diversified components, it gives the core-shell composite material rich physical and chemical properties, showing broad application prospects in different fields. For example, in the field of energy storage and conversion, the design of surface functional layers based on oxides, phosphates, etc. has been widely used in protecting active materials and improving material stability and performance. Starting from the actual functional requirements of the material and based on the exploration of synthetic methods, the precise construction of a specific core-shell structure has become the basis and key to give full play to its structural advantages and clarify the structure-activity relationship of the core-shell structure.

[0003] The precise construction of core-shell structures depends on the regulation of the deposition and growth process of shell species on the target substrate surface. Starting from the scale-up preparation and application requirements of core-shell structure materials, based on the regulation of liquid phase reactions, the core-shell structure is directly obtained through the control of growth kinetics in solution, which becomes a reliable means to achieve material preparation. For the growth process of different materials, how to overcome their own rapid precipitation trend and make the target species heterogeneously nucleate and grow on the surface of the substrate material has become a challenge and core issue in the research of core-shell structure preparation methods. For example, for metal oxide species, how to control the precipitation mode and precipitation rate of metal ions so that their growth process meets the needs of heterogeneous nucleation has become the focus of research. At the same time, in order to achieve the effective performance of the core-shell structure, the preparation of materials needs to fully consider the stability of the substrate material in the solution to ensure the non-destructive surface growth control of the substrate material. For example, surface coating treatment has become an effective means to improve the stability of high-nickel positive electrode materials for lithium-ion batteries. However, this positive electrode material is very sensitive to water, and the wet coating process based on water solvents can easily cause rapid attenuation of the material capacity. Therefore, it is of great research significance to develop a liquid phase synthesis method of non-aqueous solvents to achieve damage-free coating treatment on the surface of high-nickel positive electrode materials. Summary of the invention

[0004] The purpose of the present invention is to provide a method for accurately and non-destructively constructing a coating layer with controllable thickness on the surface of a material in a non-aqueous solvent. The method has simple process, mild reaction conditions, strong universality, and can achieve accurate and non-destructive treatment effects on the surface of nuclear materials, especially in the field of high-energy storage devices, namely lithium-ion batteries or lithium batteries, which has high practicality and application prospects.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a coating method for constructing a metal-containing coating layer, comprising the following steps:

[0007] S1, adding a coating substrate material, a coordination agent and an initiator into a non-aqueous solvent to obtain a mixed solution;

[0008] S2, adding an organic metal salt to the mixed solution, stirring and reacting to form a metal-containing coating layer on the surface of the coating substrate material.

[0009] In step S1, the non-aqueous solvent is an anhydrous alcohol solvent and / or an anhydrous ketone solvent, preferably at least one of methanol, anhydrous ethanol, isopropanol, ethylene glycol, propylene glycol, n-propanol, n-butanol and acetone, more preferably anhydrous ethanol.

[0010] The purity of the non-aqueous solvent is chromatographically pure, and its water content is ≤0.1 wt%.

[0011] The present invention does not specifically limit the coating substrate material, which can be at least one of a metal element and its alloy, oxide, carbide, sulfide, phosphide, nitride, lithium salt, phosphate, non-metal element and organic particles;

[0012] Wherein, the metal is selected from at least one of the following metals and their alloys: gold, silver, palladium, platinum, ruthenium, rhodium, tin, germanium and antimony;

[0013] The oxide is selected from at least one of silicon dioxide, tin dioxide, aluminum oxide, molybdenum oxide, vanadium pentoxide, titanium dioxide, manganese tetraoxide, cobalt tetraoxide, zirconium dioxide, zinc oxide, cerium dioxide, magnesium oxide, calcium oxide, indium oxide, gallium oxide, lithium oxide, iron oxide and lithium lanthanum zirconium oxide; preferably silicon dioxide;

[0014] Wherein, the carbide is selected from at least one of calcium carbide, titanium carbide, chromium carbide, vanadium carbide, tungsten carbide, silicon carbide, boron carbide and tantalum carbide;

[0015] The sulfide is selected from at least one of molybdenum sulfide, zinc sulfide, nickel sulfide, cobalt sulfide, bismuth sulfide, tin sulfide, tungsten sulfide, antimony sulfide and titanium disulfide;

[0016] Wherein, the phosphide is selected from at least one of cobalt phosphide, molybdenum phosphide, titanium phosphide, nickel phosphide, iron phosphide and tin phosphide;

[0017] Wherein, the nitride is selected from at least one of gallium nitride, boron nitride, silicon nitride, phosphorus nitride, tungsten nitride, vanadium nitride, titanium nitride, niobium nitride and lithium nitride;

[0018] Wherein, the lithium salt is selected from at least one of lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt oxide, lithium-rich nickel cobalt manganese oxide and lithium titanate; preferably at least one of lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium-rich nickel cobalt manganese oxide;

[0019] The phosphate is selected from at least one of iron phosphate, peptide phosphate, peptide lithium, peptide aluminum lithium, lithium iron phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese cobalt phosphate, lithium iron manganese phosphate, lithium vanadium phosphate and sodium vanadium phosphate;

[0020] Wherein, the non-metallic element is selected from at least one of carbon, carbon nanotubes, graphene, graphite, graphene oxide, fullerene, silicon, phosphorus, sulfur, selenium, tellurium and boron;

[0021] Wherein, the organic particles are selected from at least one of polystyrene, phenolic resin, urea-formaldehyde resin, melamine resin, polyvinyl pyrrolidone, polydopamine, glucose, chitosan and fructose.

[0022] The average particle size of the coated substrate material is 10 nm-100 μm; for example, 20 nm-50 μm, 50 nm-10 μm, 100 nm-1 μm; illustratively, the average particle size is 500 nm or 800 nm.

[0023] The ligand is one or more of alkanoic acid, dilute acid, acetylic acid, alkylamine, dilute amine, acetylenic amine, thiol, fluoroalkane, alkylphosphoric acid, alkenylphosphonic acid and acetylenic phosphonic acid, preferably one or more of hexadecylamine, octadecanoic acid, dodecylphosphonic acid, 1-fluorododecane and hexadecylmercaptan.

[0024] The initiator is deionized water and / or ammonia water, wherein the mass concentration of the ammonia water is 25%-28%.

[0025] In the mixed solution, the concentration of the coated substrate material is 0.001-1000 g / L; for example, the concentration is 0.05-50 g / L, 1-10 g / L; illustratively, the concentration is 2 g / L, 5 g / L, 8 g / L.

[0026] In the mixed solution, the concentration of the complexing agent is 1×10 -5 -1 mol / L, more preferably 1×10 -4 -0.03mol / L.

[0027] In the mixed solution, the concentration of the initiator is 1-100 mL / L, more preferably 5-20 mL / L.

[0028] In step S2, the organic metal salt is one or more of metal alkoxide, acetylacetonate and ethoxylate, preferably metal alkoxide, more preferably niobium ethoxide or tantalum ethoxide.

[0029] The molar ratio of the organic metal salt to the coated substrate material is (0.001-100):1; preferably (0.005-1):1.

[0030] The stirring reaction conditions are: temperature of -10-100°C, such as 0-50°C, illustratively, the temperature is 25°C, time is 10min-48h, such as 20min-10h, illustratively, time is 0.5h, 2h.

[0031] In a second aspect, the present invention further provides a method for preparing core-shell structured coated particles, comprising the following steps:

[0032] (1) forming a metal-containing coating layer on the surface of the coated substrate material by the above-mentioned coating method, and obtaining a coated material by centrifugation, washing and drying;

[0033] (2) calcining the coating material to obtain core-shell structured coated particles.

[0034] In step (1), the drying conditions are: temperature of 75-85°C, exemplarily, temperature of 80°C, time of 7-9h, exemplarily, time of 8h.

[0035] In step (2), the calcination conditions are: temperature of 300-1000°C, for example, temperature of 400-900°C, illustratively, temperature of 500°C, 600°C, 700°C, 800°C; time of 0.5-30h, illustratively, 1h, 2h, 4h, 10h, 20h.

[0036] In step (2), the calcination atmosphere is at least one of air, oxygen, nitrogen, argon, and a hydrogen / argon mixture; illustratively, air or oxygen is selected.

[0037] In step (2), the coating material is mixed with a lithiation agent and then calcined; the lithiation agent is lithium hydroxide or lithium carbonate. The molar ratio of the coating material to the lithiation agent is 1:(1-1.1), such as 1:(1-1.08), 1:(1.02-1.06).

[0038] In a third aspect, the present invention further provides core-shell structure coated particles obtained by the above method; the core-shell structure coated particles are composed of a core and a shell layer.

[0039] The material of the core is the coating substrate material.

[0040] The material of the shell layer is one of metal oxides, phosphates, metal fluorides and metal sulfides.

[0041] The metal oxide is one or more of niobium pentoxide, zirconium dioxide, tantalum pentoxide, aluminum trioxide, iron tetroxide and titanium dioxide.

[0042] The phosphate is one or more of aluminum phosphate, niobium phosphate, zirconium phosphate, tantalum phosphonate and cobalt phosphate.

[0043] The metal fluoride is one or more of niobium pentafluoride, aluminum trifluoride, titanium tetrafluoride and tantalum pentafluoride.

[0044] The metal sulfide is one or more of zinc sulfide, aluminum sulfide, iron sulfide and calcium sulfide.

[0045] The shell layer has a thickness of 0.5-200 nm, such as 1-100 nm, 3-50 nm, and illustratively, the thickness is 3 nm, 5 nm, 9 nm, 12 nm, 24 nm, or 38 nm.

[0046] Preferably, the core-shell structure coated particles are carbon spheres coated with niobium pentoxide, silicon dioxide coated with tantalum pentoxide, polystyrene coated with niobium pentafluoride, zirconium dioxide coated with niobium sulfide, lithium nickel cobalt manganese oxide coated with aluminum trioxide, and lithium nickel manganese oxide coated with aluminum phosphate.

[0047] In a fourth aspect, the present invention further provides a lithium-ion battery, comprising a positive electrode and a negative electrode; the positive electrode comprises a positive electrode material, a binder and a conductive agent; the positive electrode material is the above-mentioned core-shell structure coated particles.

[0048] When the coating substrate material is a lithium salt, the core-shell structure coated particles obtained after calcining the coating material can be directly used as positive electrode materials. When the coating substrate material is a positive electrode material precursor, the positive electrode material is the core-shell structure coated particles obtained by mixing the coating material with a lithium reagent and then calcining.

[0049] The beneficial effects achieved by the present invention are as follows:

[0050] 1. The present invention provides a method for accurately constructing a metal oxide, phosphate, fluoride or sulfide coating layer in a non-aqueous solvent. First, based on the reaction environment provided by the non-aqueous solvent, the ion activity of the reactant can be weakened and the excessive hydrolysis of the metal ions can be inhibited; secondly, a ligand is used to further stabilize the reaction environment of the metal ions, effectively control the precipitation process of the metal salt, so that the hydrolysis product is continuously and evenly deposited on the surface of the coated substrate material, and the precipitation mode of the precipitate is adjusted, thereby obtaining a uniform, continuous and complete coating layer on the surface of the substrate material, and the thickness can be controlled within the nanometer precision range, while the surface of the coated substrate material is intact; finally, the metal oxide, phosphate, fluoride or sulfide coated core-shell structure particles can be obtained by further calcination treatment.

[0051] 2. The method provided by the present invention has simple process, mild reaction conditions, strong universality, can achieve accurate and non-destructive treatment effect on the surface of nuclear materials, and has a wide range of applications.

[0052] 3. The coated positive electrode material obtained by in-situ thickness-controlled coating of the positive electrode material of a lithium-ion battery or a lithium battery by the coating method provided by the present invention has excellent electrochemical properties and can be used as the positive electrode material of a lithium-ion battery or a lithium battery of a high-energy energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a transmission electron microscope (TEM) image of the carbon sphere particles coated with niobium pentoxide in Example 1.

[0054] Figure 2 This is a transmission electron microscope (TEM) image of the silicon dioxide particles coated with tantalum pentoxide in Example 2.

[0055] Figure 3 This is a transmission electron microscope (TEM) image of the polystyrene particles coated with niobium pentafluoride in Example 3.

[0056] Figure 4 This is a transmission electron microscope (TEM) image of the zirconium dioxide particles coated with niobium sulfide in Example 4.

[0057] Figure 5 This is a transmission electron microscope (TEM) image of the aluminum oxide-coated lithium nickel cobalt manganese oxide particles in Example 5.

[0058] Figure 6 This is a transmission electron microscope (TEM) image of the aluminum phosphate-coated lithium nickel manganese oxide particles in Example 6.

[0059] Figure 7 This is a high-resolution transmission electron microscopy (HRTEM) image of the aluminum phosphate-coated lithium nickel manganese oxide particles in Example 6.

[0060] Figure 8 This is a transmission electron microscope (TEM) image of carbon sphere particles coated with niobium pentoxide in Comparative Example 1 when no coordination agent is added.

[0061] Fig. 9 It is the cycle diagram of the lithium nickel manganese oxide positive electrode material in the application example and comparative example 2 at 1C rate. DETAILED DESCRIPTION

[0062] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0063] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0064] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.

[0065] Example 1 Preparation of carbon sphere particles coated with niobium pentoxide

[0066] Here are the steps:

[0067] (1) At 25°C, 5 mg of carbon spheres (average particle size of 100 nm), 20 mg of tetradecylamine, and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0068] (2) adding 25 μL of niobium ethanol to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coated material;

[0069] (3) The obtained coated material was calcined at 300° C. for 2 h in an air atmosphere to obtain carbon sphere particles coated with niobium pentoxide having a core-shell structure.

[0070] Example 2 Tantalum pentoxide coated silicon dioxide particles

[0071] Here are the steps:

[0072] (1) At 25° C., 5 mg of silicon dioxide (average particle size of 150 nm), 20 mg of tetradecylamine, and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0073] (2) adding 25 μL of tantalum ethoxide to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coating material;

[0074] (3) The obtained coated material was calcined at 300° C. for 2 h in an air atmosphere to obtain tantalum pentoxide-coated silicon dioxide particles with a core-shell structure.

[0075] Example 3 Niobium Pentafluoride-Coated Polystyrene Particles

[0076] Here are the steps:

[0077] (1) At 25°C, 5 mg of polystyrene beads (average particle size of 500 nm), 20 mg of 1-fluoro-12-oxane, and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0078] (2) adding 25 μL of niobium ethanol to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coated material;

[0079] (3) The obtained coated material was calcined at 300° C. for 2 h in an air atmosphere to obtain polystyrene particles coated with niobium pentafluoride having a core-shell structure.

[0080] Example 4 Niobium sulfide coated zirconium dioxide particles

[0081] Here are the steps:

[0082] (1) At 25° C., 5 mg of nano-sized zirconium dioxide (average particle size of 50 nm), 20 mg of 1-octadecanethiol, and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0083] (2) adding 25 μL of niobium ethanol to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coated material;

[0084] (3) The obtained coated material was calcined at 300° C. for 2 h in an air atmosphere to obtain niobium sulfide-coated zirconium dioxide particles with a core-shell structure.

[0085] Example 5 Aluminum oxide coated lithium nickel cobalt manganese oxide particles

[0086] Here are the steps:

[0087] (1) At 25° C., 5 mg of lithium nickel cobalt manganate (average particle size of 2 μm), 20 mg of tetradecylamine, and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0088] (2) adding 25 mg of aluminum isopropoxide to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coated material;

[0089] (3) The obtained coated material was calcined at 300° C. for 2 h in an air atmosphere to obtain aluminum oxide-coated lithium nickel cobalt manganese oxide particles with a core-shell structure.

[0090] Example 6 Aluminum phosphate coated lithium nickel manganese oxide particles

[0091] Here are the steps:

[0092] (1) At 25° C., 5 mg of lithium nickel manganese oxide (average particle size of 2 μm), 20 mg of dodecylphosphonic acid, and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0093] (2) adding 25 mg of aluminum isopropoxide to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coated material;

[0094] (3) The obtained coated material was calcined at 700° C. in an air atmosphere for 2 h to obtain aluminum phosphate-coated lithium nickel manganese oxide particles with a core-shell structure.

[0095] Example 7 Aluminum phosphate coated high nickel cathode material containing a lithiation step

[0096] Here are the steps:

[0097] (1) At 25°C, 5 mg of high nickel ternary precursor (molecular formula Ni 0.80 Co 0.10 Mn 0.10 (OH)2), 20 mg tetradecylamine and 0.1 ml water were mixed evenly in 10 ml anhydrous ethanol to obtain a mixed solution;

[0098] (2) adding 25 mg of aluminum isopropoxide to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a coated material;

[0099] (3) The obtained coating material was mixed with lithium hydroxide monohydrate at a molar ratio of 1:1.05, and calcined at 900° C. for 10 h in an oxygen atmosphere to obtain a lithiated aluminum phosphate-coated high-nickel positive electrode material.

[0100] Comparative Example 1 (without adding complexing agent)

[0101] Here are the steps:

[0102] (1) At 25°C, 5 mg of carbon spheres (average particle size of 100 nm) and 0.1 ml of water were mixed in 10 ml of anhydrous ethanol to obtain a mixed solution;

[0103] (2) adding 25 μL of niobium ethoxide to the obtained mixed solution, reacting for 0.5 h, centrifuging, washing, and drying at 80° C. for 8 h to obtain a dry product;

[0104] (3) The obtained dried product was calcined at 300° C. for 2 h in an air atmosphere to obtain sintered carbon sphere particles.

[0105] Application Examples

[0106] 1. Preparation of aluminum phosphate coated lithium nickel manganese oxide electrode

[0107] The aluminum phosphate-coated lithium nickel manganese oxide particles with a core-shell structure obtained in Example 6 were used as the positive electrode material. 200 mg of the positive electrode material obtained above was mixed with 25 mg of a binder, polyvinylidene fluoride (PVDF), and 25 mg of a conductive agent, Super-P, in a mass ratio of 8:1:1. About 200 μL of N-methylpyrrolidone (NMP) was added to prepare a slurry. Aluminum foil was used as a current collector. The slurry was evenly coated on the aluminum foil with a coating thickness of 200 μm. The slurry was dried at 80°C in a vacuum oven for 12 h to obtain a positive electrode film.

[0108] 2. Assemble the battery

[0109] The prepared positive electrode film was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane (Celgard2400) was used as the separator, and 1 mol / L LiPF6 (EC:DMC:DEC=1:4:2) was used as the electrolyte to assemble a button cell in an argon-protected glove box.

[0110] Comparative Example 2

[0111] 1. Preparation of Lithium Nickel Manganese Oxide Electrode

[0112] 200 mg of original lithium nickel manganese oxide positive electrode material was mixed with 25 mg of binder polyvinylidene fluoride (PVDF) and 25 mg of conductive agent Super-P in a mass ratio of 8:1:1, and about 200 μL of N-methylpyrrolidone (NMP) was added to prepare a slurry. Aluminum foil was used as the current collector, and the slurry was evenly coated on the aluminum foil with a coating thickness of 2 μm. The cathode membrane was obtained by vacuum drying at 80°C for 12 h.

[0113] 2. Assemble the battery

[0114] The prepared positive electrode film was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane (Celgard2400) was used as the separator, and 1 mol / L LiPF6 (EC:DMC:DEC=1:4:2) was used as the electrolyte to assemble a button cell in an argon-protected glove box.

[0115] Effect verification

[0116] 1. By Figure 1-Figure 7 It can be seen that a uniform and continuous coating layer is formed on the surface of the obtained particles; the thickness of the shell layer in the core-shell structure coated particles obtained in Examples 1-6 is 80nm, 10nm, 5nm, 15nm, 6nm, and 3nm, respectively. Figure 7 It can be seen that this coating method has no obvious damage to the crystal lattice of the substrate material itself, achieving a lossless effect.

[0117] 2. By Figure 8 It can be seen that no coating layer is formed on the surface of the carbon sphere particles obtained in Comparative Example 1, indicating that the coating cannot be successfully performed without adding a complexing agent.

[0118] 3. The batteries assembled in the application example and comparative example 2 were subjected to constant current charge and discharge tests on a blue electric charge and discharge tester, with a charge and discharge rate of 1C (1C = 146.7 mA / g) and a charge and discharge range of 3.0-5.0 V. The results are as follows: Fig. 9 As shown, after 500 cycles, the capacity retention rate of the battery obtained in the application example is 88.4%, while the capacity retention rate of the battery obtained in the comparative example 2 is only 36.2%, which indicates that the positive electrode material obtained by the coating method provided by the present invention has better cycle stability.

[0119] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A coating method for constructing a metal coating layer, comprising the following steps: S1, adding a coating substrate material, a ligand and an initiator into a non-aqueous solvent to obtain a mixed solution; S2, adding an organic metal salt to the mixed solution, stirring and reacting to form a metal-containing coating layer on the surface of the coating substrate material.

2. The coating method according to claim 1, characterized in that: In step S1, the non-aqueous solvent is an anhydrous alcohol solvent and / or an anhydrous ketone solvent.

3. The coating method according to claim 1 or 2, characterized in that: In step S1, the complexing agent is one or more of alkanoic acid, dilute acid, alkyne acid, alkylamine, dilute amine, alkyne amine, thiol, fluoroalkane, alkylphosphonic acid, alkenylphosphonic acid and alkynephosphonic acid; In the mixed solution, the concentration of the complexing agent is 1×10 -5 -1mol / L.

4. The coating method according to any one of claims 1 to 3, characterized in that: In step S1, the initiator is deionized water and / or ammonia water; In the mixed solution, the concentration of the initiator is 1-100 mL / L.

5. The coating method according to any one of claims 1 to 4, characterized in that: In step S1, the average particle size of the coating substrate material is 10nm-100μm; In the mixed solution, the concentration of the coating substrate material is 0.001-1000 g / L.

6. The coating method according to any one of claims 1 to 5, characterized in that: In step S2, the organic metal salt is one or more of metal alkoxide, acetylacetonate and ethoxylate; The molar ratio of the organic metal salt to the coated substrate material is (0.001-100): 1; The stirring reaction conditions are: temperature of -10-100°C and time of 10 min-48 h.

7. A method for preparing core-shell structure coated particles, comprising the following steps: (1) forming a metal-containing coating layer on the surface of the coated substrate material by the coating method according to any one of claims 1 to 6, and obtaining a coated material by centrifugation, washing and drying; (2) calcining the coating material to obtain core-shell structured coated particles.

8. The preparation method according to claim 7, characterized in that: In step (2), the coating material is mixed with a lithiation agent and then calcined; The lithiation reagent is lithium hydroxide or lithium carbonate; The molar ratio of the coating material to the lithiation agent is 1:(1-1.1), for example, 1:(1-1.08), 1:(1.02-1.06).

9. The core-shell structure coated particles obtained by the preparation method according to claim 7 or 8.

10. A lithium ion battery comprising a positive electrode and a negative electrode; the positive electrode comprises a positive electrode material, a binder and a conductive agent; the positive electrode material is the core-shell structure coated particle according to claim 9.

Citation Information

Patent Citations

  • Powders for additive manufacturing

    CN107848029A

  • Method for constructing thickness-controllable metal oxide coating layer in solution phase

    CN112420997A

  • Method for controllably constructing sulfide coating layer

    CN114976007A

  • Method for realizing controllable construction of phosphate-containing carbon composite coating layer through polymerization method and application thereof

    CN116344806A

  • Composite oxide particles and their manufacturing method

    JP2007022827A